Insight on the choice of sensitizers/dyes for dye sensitized solar cells: A review. (May 2023) - Sen, Anik; Putra, Miftahussurur Hamidi; Biswas, Abul Kalam; Behera, Anil Kumar; Groβ, Axel
Abstract: In this review, a discussion on renewable sources of energy with clear focus on solar cell applications is presented. Especially, possible future directions for development of dye-sensitized solar cells (DSSCs) are discussed. Dye-sensitized solar cells have become an important topic of research due to its high importance in energy conversion. Current DSSCs are based on metal dye sensitizers, metal-free organic dyes or natural dyes. They have been extensively studied due to their low cost, simple preparation methodology, low toxicity, and ease of production. Still there is a need to find more abundant DSSC materials that at the same time exhibit long-term stability. Computational studies have been an important ally for developing/designing new dye sensitizers. They are reviewed here with a special emphasis on the benefit of such studies. The conceptual understanding of development and working principle of photoactive DSSC materials is the primary feature of the review followed by examples of studies on different dye sensitizers using scarce to abundant metal based dyes and metal free organic dyes with donor-π-acceptor geometries for both n- and p-type DSSCs. The proper choice of organic dyes including donor, spacer, or acceptor is discussed and a prospective on dual donor based dyes is presented. Graphical abstract: Image 1 Highlights: An understanding of solar cell applications, especially focusing on possible future directions for the development of dye sensitized solar cells. Different choices of dye sensitizers like scarce to abundant metal-based dyes; from porphyrin and phthalocyanine based dyes and also metal free organic dyes. A future prospective of dual organic donor-based dyes which may contribute to the development of new dye sensitizers with improved properties have been discussed.